Two Views of Public Participation - Blackman, H. S.; Harbour, J. L. (WM Symposia, Inc., 2002)
Risk perception has been studied extensively over the past several decades. This research has defined the differences that exist between and among various groups as defined by their education, interests, geographic distribution, and beliefs. It has also been repeatedly demonstrated that various public groups can and do have a tremendous impact on decisions made in the public and private sectors. Involved citizens for example, have caused international corporations as well as the Department of Energy to change or even reverse a chosen course of action. A frequent cause of such reversals is attributed to a lack of involvement of the public and other key decision players directly in the decision process itself. Through our research and case studies, we have developed both an ''as is'' and a ''participatory'' model of decision-making process. The latter decision model allows the direct involvement of important player groups. The paper presents and discusses these models in theoretical and practical terms taken from case studies of the Brent Spar disposal in the North Atlantic, and the use of incineration as a method of waste treatment at the Idaho National Engineering Laboratory. Results from the case studies are used to demonstrate why the ''as is'' model accurately describes the current situation, and how the ''participatory model'' will allow decisions to be made that are publicly supported and can be implemented. The use of such a model will provide users a framework from which to successfully make progress in a wide range of environmental endeavors cooperatively with the public, rather than in spite of the public.